2018
DOI: 10.1159/000494430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Utility of Immunohistochemistry Markers of TROP-2 and HBME-1 in the Diagnosis of Thyroid Carcinoma

Abstract: Objective: The diagnosis of thyroid tumors is based on histologic features, but the distinction between benign and malignant thyroid lesions is somehow difficult, especially in lesions with a follicular pattern. Thus, ancillary studies, such as immunohistochemistry (IHC), may be helpful. In this study, we aimed to evaluate the diagnostic value of 2 IHC markers, TROP-2 and HBME-1, in the diagnosis of thyroid cancers. Study Design: A total of 102 cases of thyroid lesions, including papillary thyroid carcinoma (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 13 publications
(21 reference statements)
3
23
0
Order By: Relevance
“…TROP2 possesses sites for tyrosine/serine phosphorylation that regulate signal transduction or its expression and activity, thereby rendering cancer cells resistant to apoptosis [32]. Upregulated TROP2 correlates with the poor prognosis of thyroid papillary carcinoma [33], colon cancer [34], liver cancer [35], and other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…TROP2 possesses sites for tyrosine/serine phosphorylation that regulate signal transduction or its expression and activity, thereby rendering cancer cells resistant to apoptosis [32]. Upregulated TROP2 correlates with the poor prognosis of thyroid papillary carcinoma [33], colon cancer [34], liver cancer [35], and other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…As for the thyroid tumors, the previous studies have shown the potential utility of TROP-2 as a useful diagnostic tool for PTC in surgical and cytology specimens and the differential expression of TROP-2 in benign and malignant thyroid lesions. 6-10,22-25 Among them, Bychkov et al evaluated TROP-2 expression in a variety of thyroid cancers including PTC, FTC, insular or poorly differentiated carcinoma, and ATC. 6 Their study demonstrated most of the PTCs (94/114, 82.5%) and none of the 35 FTC cases to be immunopositive for TROP-2.…”
Section: Discussionmentioning
confidence: 99%
“…TROP2 possesses sites for tyrosine/serine phosphorylation that regulate signal transduction or regulatory factor, thereby imparting resistance to apoptosis in cancer cells [32]. Upregulated TROP2 correlates with the poor prognosis of thyroid papillary carcinoma [33], colon cancer [34], liver cancer [35], and other malignant tumors.…”
Section: Discussionmentioning
confidence: 99%